An Unromanticized Afghanistan in Saira Shahâ€™s The Storytellerâ€™s Daughter - Qutami, Mais (Mediterranean Journal of Social Sciences, 2012)
In this paper I examine Saira Shahâ€™s representation of Afghanistan and her conflicted position as a viewer andnarrator whose â€œway of seeingâ€ the East and West sometimes fluctuates between an Orientalist and a nationalist perspective. Iargue though that her affiliation to the West and Orientalist views seem to dominate her perception of Afghani culture and itspeople far more than she had expected. Despite her attempts to renegotiate her hyphenated identity, as an Afghani- British, shefinds herself unable to embrace the new torn- up Afghanistan that replaces the romanticized image she had of it in the past. InThe Storytellerâ€™s Daughter, Shah tries to bring Afghanistan and its culture to light, but indirectly contributes to its invisibility andmisrepresentation by the colonial discourse. She shares with her readers her experiences with the Taliban and the women shemet in Afghanistan which she thought of as a mysterious land until she was disillusioned with its horrific state of war and politicalturmoil.